Accuracy of soft tissue prediction in surgery-first treatment concept in orthognathic surgery: A prospective study. Issue 9 (September 2018) - Holzinger, Daniel; Juergens, Philipp; Shahim, Kamal; Reyes, Mauricio; Schicho, Kurt; Millesi, Gabriele; Perisanidis, Christos; Zeilhofer, Hans-Florian; Seemann, Rudolf
Abstract: Purpose: The purpose of this study was to provide a quantitative accuracy assessment of soft tissue predictions generated by a computer-aided maxillofacial planning system in patients undergoing orthognathic surgery following the "surgery-first" treatment. Materials and methods: For this study, we looked at 16 patients with open bite dentofacial-dysmorphosis who underwent orthognathic surgery. Surgeries were planned using conventional sketches and the newly developed computer-assisted SOTIRIOS planning software (developed by the authors). Validation procedures were performed in the following steps: (1) Standardized registration of the pre- and postoperative CT volumes; (2) Automated adjustment of the bone-related preoperative planning to the actual postoperative bony displacement; (3) Simulation of soft tissue changes according to the definitive bony movements; and (4) Calculation of soft tissue differences between the predicted and the actual 6-month postoperative results by distance mapping. Results: The program produced a clinically satisfactory 3D soft tissue prediction, with a mean error of 1.46 mm ± 1.53 mm. The program was suitable for use in virtual surgical planning without technical assistance. Conclusion: This study shows that the program is quite accurate, enabling the surgeon to predict the outcome of the soft tissue. This has the potential to promote the routine application of the surgery-first approach in patients suffering from open bite.